PENGARUH PENDIDIKAN LATIHAN DAN PENGALAMAN TERHADAP KEPUASAN KERJA GURU SEKOLAH DASAR - Listriani, Ana; Sukmawati, Sukmawati; Chiar, M (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe quality of the education process depends on the quality of the teacher based on performance. High and low teacher performance can not be separated from job satisfaction. The research aimed to obtain an overview and information on the effect of training education and experience on job satisfaction for Nageri Elementary School teachers in North Pontianak District. This study used a descriptive research method with a quantitative approach with the form of a correlation study with a sample of 32 people. In collecting research data used indirect communication techniques with closed questionnaire data collection tools. Conclusion of the research shows that: 1) Job satisfaction of Public Elementary School teachers in North Pontianak District is good; 2) Education training for public elementary school teachers in North Pontianak District is good; 3) The work experience of public elementary school teachers in North Pontianak Subdistrict is very good; 4) Education and training have a significant effect on the work satisfaction of public elementary school teachers in North Pontianak District; 5) Experience has a significant effect on the work satisfaction of public elementary school teachers in North Pontianak District; 6) Educational training and experience simultaneously have a significant effect on job satisfaction of public elementary school teachers in North Pontianak District. Â Keywords: Education Training, Experience Work, Job Satisfaction